Vaccination with inactivated SARS-CoV-2 vaccine TURKOVAC induces durable humoral and cellular immune responses up to 8 months - Yılmaz, Seçil; Eken, Ahmet; Sezer, Zafer; Bağcı, Burcu Şen; Erdem, Serife; Sarıkaya, Medine Doğan; Kaplan, Busra; Inal, Ahmet; Bayram, Adnan; Kalın Unuvar, Gamze; Zararsız, Gokmen; Yerlitas, Serra İlayda and Cakir, Nuri and Pavel, Shaikh Terkis Islam and Uygut, Muhammet Ali and Yetiskin, Hazel and Kara, Ates and Ozdarendeli, Aykut (Frontiers in Medicine, 2025)
BackgroundThe rapid spread of the SARS-CoV-2 virus has led to a global health crisis, necessitating swift responses in medical science, mainly through vaccination strategies. While short-term vaccine effectiveness is evident, immune protection’s long-term effects and duration remain incompletely understood. Systematic monitoring of these responses is essential for optimizing vaccination strategies.AimsThis study aimed to explore the durability of antigen-specific T and B cell responses and antibody levels up to 8 months post-immunization with the inactivated TURKOVAC vaccine in volunteers. Additionally, the impact of two versus three doses of vaccination on these parameters was analyzed.MethodsVolunteers (n = 80) received two or three doses of TURKOVAC. Spike-specific B cells, CD4+ T cells, CD8+ T cells, and antibody levels were measured at multiple time points post-immunization.ResultsSpike-specific B cells remained elevated up to 8 months post-immunization. SARS-CoV-2-specific CD4+ and CD8+ T cells peaked at 4 months but declined thereafter. TURKOVAC resulted in durable antigen-specific humoral and cellular immune memory with distinct kinetics. Still, most assessments observed no significant differences between two and three doses, except for antigen specific-IL-2 and CD4+ LAMP1 responses.ConclusionTURKOVAC vaccination induces durable immune responses, with spike-specific B cells persisting up to 8 months and T cell responses peaking at 4 months before declining. These findings suggest that TURKOVAC contributes to long-term immune protection against SARS-CoV-2.